2017
DOI: 10.1016/j.omtn.2017.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Control of HIV Infection In Vivo Using Gene Therapy with a Secreted Entry Inhibitor

Abstract: HIV entry inhibitors are highly effective in controlling virus replication. We have developed a lentiviral vector that expresses a secreted entry inhibitor, soluble CD4 (sCD4), which binds to the HIV envelope glycoproteins and inactivates the virus. We have shown that sCD4 was secreted from gene-modified CD4+ T cells, as well as from human umbilical cord blood-derived CD34+ hematopoietic stem/progenitor cells (HSPCs), and protected unmodified HIV target cells from infection in vitro. To investigate the in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 87 publications
(117 reference statements)
0
14
0
1
Order By: Relevance
“…In terms of their higher production cost, PPVIs are Deen et al, 1988;Traunecker et al, 1988;Daar et al, 1990;Orloff et al, 1993 generally more expensive for long-term treatment of chronic viral infection. Lentiviral vector-based gene therapy to secret a PPVI continuously can be one choice to lower the cost (Perez et al, 2005;Egerer et al, 2011;Falkenhagen et al, 2014Falkenhagen et al, , 2017. For example, Falkenhagen et al (2014) designed lentiviral vectors encoding secreted anti-HIV proteins including sCD4, which could prohibit the infection of both gene-modified and unmodified cells.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of their higher production cost, PPVIs are Deen et al, 1988;Traunecker et al, 1988;Daar et al, 1990;Orloff et al, 1993 generally more expensive for long-term treatment of chronic viral infection. Lentiviral vector-based gene therapy to secret a PPVI continuously can be one choice to lower the cost (Perez et al, 2005;Egerer et al, 2011;Falkenhagen et al, 2014Falkenhagen et al, , 2017. For example, Falkenhagen et al (2014) designed lentiviral vectors encoding secreted anti-HIV proteins including sCD4, which could prohibit the infection of both gene-modified and unmodified cells.…”
Section: Discussionmentioning
confidence: 99%
“…Directly after infection, viral load and percentages of CD4 + T cells were similar between the control and sCD4 groups. 119 In control mice, viral load continued to increase and the percentage of CD4 + T cells decreased. 119 In contrast, viral load continuously decreased and the percentage of CD4 + T cells remained stable in mice expressing sCD4, indicating that constitutive expression and secretion of an entry inhibitor can control HIV replication in vivo .…”
Section: Main Textmentioning
confidence: 98%
“… 119 In contrast, viral load continuously decreased and the percentage of CD4 + T cells remained stable in mice expressing sCD4, indicating that constitutive expression and secretion of an entry inhibitor can control HIV replication in vivo . 119 …”
Section: Main Textmentioning
confidence: 98%
“…Our recent study to extend the results using NOJ mice engrafted with shPromA-transduced CD34 + cells and their derivatives further demonstrated that PromA could be an effective gene therapy for protecting bone marrow CD34 + cells and the hematopoietic potential of the host from HIV infection ( Figure 3B) [20,98]. Other potential gene therapy methods include the secretion of soluble HIV entry inhibitors [99]; rescue of hematopoiesis including myelopoiesis, erythropoiesis, and megakaryopoiesis using c-mpl [100]; expression of a chimeric human-simian TRIM5α [101]; expression of p68 kinase [102]; and expression of HIV Gag mutants [103]. [92] and Mendez et al, 2018 [97].…”
Section: Gene Therapy Strategies Against Hivmentioning
confidence: 99%